Conversion of English Loanwords in Bangla (The Chittagong University Journal of Arts & Humanities, 2026)
Abstract: Though there are debates among researchers about the actual domain of ‘Conversion’, it has traditionally been included and discussed in Morphology. Morphologists define ‘Conversion’ as a linguistic process of word-formation triggered by zero affixation. It means that conversion takes place when a word changes its category or parts of speech without the addition of prefixes or suffixes. This process is pervasive in the English language. In this article, by employing the Qualitative Method, we try to trace the presence of conversion and its types in some English words borrowed into Bangla. Light will also be shed on the contribution of conversional loans from the English tongue. The data collected chiefly from lexicographical sources reveal that the morphological phenomenon of conversion of English loanwords in Bangla mainly concerns three major categories - nouns, verbs and adjectives. Apart from these word classes, we also notice the conversion of some closed classes like (English) prepositions, interjections and conjunctions in Bangla. The productivity of the process is visible in the recipient language in the conversion of even non-morphematic elements like acronyms and initialisms. The most noticeable contribution of these loanwords and the process of conversion is that they have triggered the creation of some new lexemes in Bangla that are convertible, for example, ‘Bkash’, ‘Rocket’ and ‘Nagad’. These analogically created words can experience word-class shift like their English counterparts. Their travel from the nominal class to the verbal class is accomplished with much ease, almost like the English words using zero-morpheme.